Pulmonary Manifestations of Collagen Vascular Disease - Dokwal, CP (Pulse, 2011)
The collagen vascular diseases (CVDs) include a heterogeneous group of chronic inflammatory immunologically-mediated systemic diseases, such as rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), systemic sclerosis (SSc), Sjogrens syndrome, polymyositis (PM)/dermatomyositis (DM), and mixed connective tissue disease (MCTD). They present with a wide range of clinical manifestations. The clinical features in CVDs frequently overlap, causing much clinical confusion. The lung is frequently affected in CVDs and cause significant morbidity and mortality. The common pulmonary manifestations include pleural disease, pulmonary fibrosis, bronchiolitis obliterans, obliterans, organizing pneumonia, bronchiectasis, aspiration pneumonia, and diaphragmatic weakness. In the following paragraphs, the pulmonary manifestations in various collagen vascular diseases are discussed. DOI: http://dx.doi.org/10.3329/pulse.v4i1.6958 Pulse Vol.4 January 2010 p.16-21